2020
DOI: 10.3390/cancers12123708
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of Squamous Cancer Cell Collective Invasion by FAK Inhibition Is Released by CAFs and MMP-2

Abstract: Metastasis remains a clinically unsolved issue in cancer that is initiated by the acquisition of collective migratory properties of cancer cells. Phenotypic and functional heterogeneity that arise among cancer cells within the same tumor increase cellular plasticity and promote metastasis, however, their impact on collective cell migration is incompletely understood. Here, we show that in vitro collective cancer cell migration depends on FAK and MMP-2 and on the presence of cancer-associated fibroblasts (CAFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Table 1 summarises the main studies that revealed the correlations between MMP expression and clinical parameters mainly by collecting TCGA data. The results obtained support the roles of some MMPs as diagnostic, prognostic and therapeutic biomarkers in HNC patients [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Mmps and Hncsupporting
confidence: 73%
See 1 more Smart Citation
“…Table 1 summarises the main studies that revealed the correlations between MMP expression and clinical parameters mainly by collecting TCGA data. The results obtained support the roles of some MMPs as diagnostic, prognostic and therapeutic biomarkers in HNC patients [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Mmps and Hncsupporting
confidence: 73%
“…Table 1 summarises the main studies that revealed the correlations between MMP expression and clinical parameters mainly by collecting TCGA data. The results obtained support the roles of some MMPs as diagnostic, prognostic and therapeutic biomarkers in HNC patients [44][45][46][47][48][49]. TCGA: The Cancer Genome Atlas; HNSCC: head and neck squamous cell carcinoma; FAK: focal adhesion kinase; PLAU1: urokinase-type plasminogen activator.…”
Section: Mmps As Therapeutic Targets and Prognostic Biomarkers In Hnsccsupporting
confidence: 71%
“…The role of matrix-metalloproteinases (MMPs) on the stimulation of invasion and angiogenesis is well established [54]. It has been shown that MMP-9 and MMP-2 released from CAFs can stimulate the potential of invasion and migration in carcinoma cells [55,56]. Through our invasion model, we demonstrated the migration inhibitory effect of CAFs.…”
Section: Discussionmentioning
confidence: 74%
“…FAK participates in the integrin-mediated formation of adhesion plaque, which regulates cell adhesion and migration. FAK KO suppresses the cell migration of fibroblasts ( 43 ). In addition, the previous excellent study clearly shows that sialylation of β1 integrin plays an important role in cell migration ( 44 ).…”
Section: Resultsmentioning
confidence: 99%